An investigation into the displacement of Permanent Survey Marks in the Hillcrest area resulting from reactive soils - Filmer, Michael; Sandford, G. (Spatial Sciences Institute, Australia, 2007)
Reactive soils in the Adelaide suburb of Hillcrest (South Australia) have resulted in concrete Permanent Survey Marks (PSMs) being horizontally displaced. This has been identified by different surveys over the past 50 years showing differences in relative measurement between PSMs. It has been assumed that this movement relates directly to the seasonal wetting and drying of reactive soils found in the area. A monitoring project was established, which found that minimal movement occurred within the 10 month study period. The results suggest that any substantial horizontal displacement previously identified is a gradual movement occurring over a number of years rather than seasonally.